Ocular blood flow evaluation by laser speckle flowgraphy in pediatric patients with anisometropia - Itokawa, Takashi; Matsumoto, Tadashi; Matsumura, Saiko; Kawakami, Momoko; Hori, Yuichi (Frontiers in Public Health, 2023)
Purpose: To determine the differences and reproducibility of blood flow among hyperopic anisometropic, fellow, and control eyes. Methods: We retrospectively studied 38 eyes of 19 patients with hyperopic anisometropia (8.2±3.0 years of age) and 13 eyes of eight control patients (6.8±1.9 years). We measured the optic nerve head (ONH) and choroidal circulation using laser speckle flowgraphy (LSFG) and analyzed the choroidal mean blur rate (MBR-choroid), MBR-A (mean of all values in ONH), MBR-V (vessel mean), MBR-T (tissue mean), and sample size (sample), which are thought to reflect the ONH area ratio, area ratio of the blood stream (ARBS). We then assessed the coefficient of variation (COV) and intraclass correlation coefficient (ICC) and compared the differences among amblyopic, fellow, and control eyes in MBR, sample, and ARBS. Results: The ONH, MBR-A, MBR-T, and ARBS of amblyopic eyes were significantly higher than those of fellow eyes (P<0.01, P<0.05, and P<0.05, respectively) and control eyes (MBR-A and ARBS, P<0.05, for both comparisons). The sample-T (size of tissue component) in amblyopic eyes was significantly smaller than that in fellow and control eyes (P<0.05). Blood flow in the choroid did not differ significantly between the eyes. The COVs of the MBR, sample, and ARBS were all ≤10%. All ICCs were ≥0.7. The COVs of pulse waveform parameter fluctuation, blowout score (BOS), blowout time (BOT), and resistivity index (RI) in the ONH and choroid were ≤10%. Conclusion: The MBR value of the LSFG in children exhibited reproducibility. Thus, this method can be used in clinical studies. The MBR values of the ONH in amblyopic eyes were significantly high. It has been suggested that measuring ONH blood flow using LSFG could detect the anisometropic amblyopic eyes.